Anti-coccidial effect of essential oil blends and vitamin D on broiler chickens vaccinated with purified mixture of coccidian oocyst from Eimeria tenella and Eimeria maxima. (19th February 2019) - Upadhaya, Santi Devi; Cho, Suk Hyeon; Chung, Thau Kiong; Kim, In Ho
ABSTRACT: A total of 800 1-day-old Ross 308 male broiler chicks were used in a 5-wk feeding trial to evaluate the effects of commercial feed additive that is composed of blends of essential oil (EO; CRINA Poultry, DSM) and vitamin D3. The birds were randomly assigned to 5 treatments with 10 replicate cages; each stocked with 16 birds and was fed corn–soybean-meal-based basal diet. Dietary treatments included: CON, unvaccinated birds fed basal diet/control; CCO, CON + coccidian oocysts vaccinated birds; EOD1, CCO + Essential oil blends and vitamin D/Prototype 1 (50 μg 25-OH-D3/kg diet, 15 mg CRINA Poultry/kg diet); EOD2, CCO + Prototype 2 (69 μg 25-OH-D3/kg diet, 30 mg CRINA Poultry/kg diet); and EOD3, CCO + Prototype 3 (138 μg 25-OH-D3/kg diet, 50 mg CRINA Poultry/kg diet). On day 7, all birds, except CON, were inoculated with 300 to 500 purified sporulated viable oocysts from Eimeria tenella and Eimeria maxima . As a result of this study, the supplementation of EO blends with vitamin D3 showed trends in improvement ( P = 0.075) body weight gain (BWG) compared with CON and CCO during the grower phase (day 7 to 21). An increase ( P < 0.05) in BWG and reduction ( P < 0.05) in feed conversion ratio (FCR) were observed in birds fed EOD2 diet during day 21 to 35 compared with vaccinated birds without feed additive. The cumulative performance during overall period (day 1 to 35) also showed that BWG was increased and FCR was reduced in EOD2 and EOD3 compared with CON, CCO, and EOD1. Furthermore, the apparent total tract digestibility of dry matter tended ( P = 0.06) to increase in EOD2 and EOD3 compared with CON and other treatments. The EOD2 and EOD3 treatments showed increased ( P < 0.05) excreta Lactobacillus counts than EOD1. The intestinal lesion score induced by E. tennela in gastro-intestinal tract was lower ( P < 0.05) in EOD1, EOD2, and EOD3 treatments compared with CCO. In conclusion, blends of EO and vitamin D3 could be used as anti-coccidial feed additive in broilers with coccidian infection.